DIAGNOSTIC ACCURACY OF RESISTIVE INDEX IN DOPPLER IMAGING IN DIAGNOSING MALIGNANT AND BENIGN ADNEXAL MASSES - Irshad, Nadia; Arshad, Ammara; Nasrullah, Zahra (Pakistan Armed Forces Medical Journal, 2021)
Objective: To evaluate the diagnostic accuracy of resistive index in Doppler Imaging in diagnosing benign and malignant adnexal masses, taking Histopathology as Gold standard.Study Design: Prospective observational study.Place and Duration of Study: Department of Radiology, Jinnah Hospital, Lahore Pakistan, from Jan to Jun 2018.Methodology: A sample size of 200 patients was calculated using WHO calculator. Patients were selected through non probability consecutive sampling. After taking informed consent and relevant history, trans-abdominal Doppler Ultrasound of the patients with adnexal masses, using 3.5 MHz transducer on Logic 5 GE Doppler Ultrasound machine was performed. The Resistive Index (RI) was calculated in every case and threshold Resistive Index of 0.4 was used to differentiate benign from malignant lesions. Patients were followed after one month. Data analysis was done using SPSS version 24. Post stratification chi-square test was applied. A p-value ≤0.05 was considered significant.Results: Total 200 patients were included in study. Mean age of patients was 40.53 ± 10.54 years. Mean size of lesion was 28.72 ± 11.48 SD. Diagnostic parameters of doppler imaging were sensitivity 91.3%, specificity 90.59%, positive predictive value 92.92% and negative predictive value 88.51%. ROC curve analysis showed 91% diagnostic accuracy of doppler imaging in diagnosing malignant and benign adnexal masses.Conclusion: Resistive index in doppler Imaging is the non-invasive modality of choice with high diagnostic accuracy in differentiating benign and malignant adnexal masses, and has not only dramatically improved our ability of differentiating benign and malignant adnexal masses pre-operatively but also helps the surgeons for proper decision making.